Lots of Copies Keep Stuff Safe as a Cooperative Archiving Solution for E-Journals - Victoria A. Reich (Issues in Science and Technology Librarianship, 2002)
The LOCKSS model, based on analysis of the history of cultural continuity epitomized by "Lots of Copies Keeps Stuff Safe," creates low-cost, persistent digital "caches" of e-journal content housed locally at institutions that have authorized access to that content and actively choose to preserve it. Accuracy and completeness of LOCKSS caches is assured through a peer-to-peer polling system (operated through LCAP, LOCKSS' communication protocol), which is both robust and secure. The creation of such caches, given the requirement that the caching library already have the right through subscription to obtain that content, has met with a high degree of publisher and library engagement and commitment.